Menstrual health and period poverty among young people who menstruate in the Barcelona metropolitan area (Spain): protocol of a mixed-methods study - Medina-Perucha, Laura; Jacques-Aviñó, Constanza; Valls-Llobet, Carme; Turbau-Valls, Rosa; Pinzón, Diana; Hernández, Lola; Canseco, Paula Briales; López-Jiménez, Tomàs; Lizarza, Enara Solana; Feliu, Jordina Munrós; Berenguera, Anna (BMJ Open, 2020)
Introduction The importance of menstrual health has been historically neglected, mostly due to taboos and misconceptions around menstruation and androcentrism within health knowledge and health systems around the world. There has also been a lack of attention on ‘period poverty’, which refers to the financial, social, cultural and political barriers to access menstrual products and education. The main aim of this research is to explore menstrual health and experiences of period poverty among young people who menstruate (YPM). Methods and analysis This is a convergent mixed-methods study, which will combine a quantitative transversal study to identify the prevalence of period poverty among YPM (11–16 years old), and a qualitative study that will focus on exploring menstruation-related experiences of YPM and other groups (young people who do not menstruate (YNM); primary healthcare professionals; educators and policy-makers). The study will be conducted in the Barcelona metropolitan area between 2020 and 2021. Eighteen schools and 871 YPM will be recruited for the quantitative study. Sixty-five YPM will participate in the qualitative study. Forty-five YNM and 12 professionals will also be recruited to take part in the qualitative study. Socioeconomic and cultural diversity will be main vectors for recruitment, to ensure the findings are representative to the social and cultural context. Descriptive statistics will be performed for each variable to identify asymmetric distributions and differences among groups will be evaluated. Thematic analysis will be used for qualitative data analyses Ethics and dissemination Several ethical issues have been considered, especially as this study includes the participation of underage participants. The study has received ethical approval by the IDIAPJGol Research Ethics Committee (19/178 P). Research findings will be disseminated to key audiences, such as YPM, YNM, parents/legal tutors, health professionals, educators, youth (and other relevant) organisations, general community members, stakeholders and policy-makers, and academia.
Keywords: 2000 à aujourd'hui; 2020-2029; adolescentes*; discipline; espagne; europe; médecine; projet charge mentale; périodes historiques; régions géographiques; santé; santé menstruelle; santé publique; thématiques

Prendre en compte le sexe et le genre dans le choix des situations à analyser : un enjeu pour l’intervention ergonomique - Laberge, Marie; Caroly, Sandrine (Perspectives interdisciplinaires sur le travail et la santé, 2016)
Le sexe/genre (s/g) doit être pris en compte dans le domaine de la santé au travail, puisque les hommes et les femmes n’occupent pas les mêmes emplois et ne sont pas exposés de la même façon aux risques de santé et sécurité au travail (SST). Cet article propose une réflexion sur les manières de considérer le s/g dans l’intervention ergonomique, en particulier lors des investigations préliminaires. Deux exemples issus d’interventions réalisées en France et au Québec sont présentés. Le premier exemple porte sur l’activité des médecins du travail dans la prévention des troubles musculosquelettiques (TMS). Le second traite du développement et de l’implantation d’une formation portant sur la SST. Dans les deux cas, ces questions portées par les ergonomes chercheuses ont permis de transformer la compréhension des dimensions liées aux parcours de santé, de travail et de vie personnelle pour que la prévention des lésions tienne compte des particularités des hommes et des femmes.
Keywords: amériques; discipline; ergonomie; europe; france; médecine; projet charge mentale; québec; ressource en ligne; régions géographiques; santé; santé au travail; sciences; thématiques; travail

From gender bias to gender awareness in medical education - Verdonk, Petra; Benschop, Yvonne W. M.; de Haes, Hanneke C. J. M.; Lagro-Janssen, Toine L. M. (Advances in Health Sciences Education, 2009)
Gender is an essential determinant of health and illness. Gender awareness in doctors contributes to equity and equality in health and aims towards better health for men and women. Nevertheless, gender has largely been ignored in medicine. First, it is stated that medicine was ‘gender blind’ by not considering gender whenever relevant. Secondly, medicine is said to be ‘male biased’ because the largest body of knowledge on health and illness is about men and their health. Thirdly, gender role ideology negatively influences treatment and health outcomes. Finally, gender inequality has been overlooked as a determinant of health and illness. The uptake of gender issues in medical education brings about specific challenges for several reasons. For instance, the political-ideological connotations of gender issues create resistance especially in traditionalists in medical schools. Secondly, it is necessary to clarify which gender issues must be integrated in which domains. Also, some are interdisciplinary issues and as such more difficult to integrate. Finally, schools need assistance with implementation. The integration of psychosocial issues along with biomedical ones in clinical cases, the dissemination of literature and education material, staff education, and efforts towards structural embedding of gender in curricula are determining factors for successful implementation. Gender equity is not a spontaneous process. Medical education provides specific opportunities that may contribute to transformation for medical schools educate future doctors for future patients in future settings. Consequently, future benefits legitimize the integration of gender as a qualitative investment in medical education.
Keywords: approches et analyses; discipline; europe; formation des médecins; médecine; pays-bas; projet charge mentale; rapports sociaux de sexe; régions géographiques; santé; sciences; sexisme; stéréotypes de genre; systèmes d'oppressions; thématiques; éducation

Démédicaliser les corps, politiser les identités : convergences des luttes féministes et intersexes - Kraus, Cynthia; Perrin, Céline; Rey, Séverine; Gosselin, Lucie; Guillot, Vincent (Nouvelles Questions Féministes, 2008)
Number: 1
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; belgique; capacitisme; corps; cours; discipline; discours dominant; europe; france; féminisme interdisciplinaire; féminisme matérialiste; hétérosexisme; identités LGBTQIA2+; intersexuation; inégalités; luxembourg; marginalisation; militance; médecine; philosophie; premier cycle; psychiatrie; périodes historiques; queer; régions géographiques; santé; sciences; sciences humaines; soc2014; soc2051; sociologie; systèmes d'oppressions; thématiques; transféminisme; violences; violences médicales

Sur la noblesse et l'excellence du sexe féminin, de sa préminence sur l'autre sexe - Agrippa de Nettesheim, Henir Corneille (De l' indécence aux hommes d'accoucher les femmes et De l' obligation aux mères de nourrir leurs enfants suivi de S'il est des signes qui assurent de la puissance des hommes, autant que le font ceux qui répondent de la sagesse des filles, 1990)
Le texte d'Henri Corneille Agrippa, Discours abrégé sur la noblesse et l'excellence du sexe féminin, de sa prééminence sur l'autre sexe, n'est pas seulement une contribution importante à l'histoire du discours sur la différence des sexes : pris hors contexte, il constitue aussi une divertissante démonstration par l'absurde de l'inadéquation de l'analyse des rapports de sexe en termes de déduction par rapport à des attributs (imaginaires ou réels) qui en constitueraient l'essence. Réédition d'après l'éd. de 1744, dont l'orthographe et la ponctuation ont été modernisés (indication de la préf. de 1990).
Première édition 1537 Donné en lecture cours FEM1000: p.28-31;98-109;111;134-137
Keywords: 1700-1799; approches et analyses; cours; discipline; europe; fem1000; france; histoire; histoire des femmes*; maternité; médecine; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sexes; thématiques

"Je me suis fait la guerre", ou comment être un "bon arabe" - Radiofrance
Dans le cabinet de la psychiatre Fatma Bouvet de la Maisonneuve, les patient.e.s se confient et notamment sur les discriminations auxquelles ils doivent faire face. Un miroir nous est tendu, s'y dessine notre société. Stéphane Mercurio nous restitue ces confidences et cet écho du monde.
Keywords: approches et analyses; cours; discipline; discours dominant; europe; fem3400; france; islam; médecine; premier cycle; psychiatrie; racisme; ressource en ligne; régions géographiques; santé; systèmes d'oppressions; thématiques; traumatismes; violences